INFLUENCE OF DEMOGRAPHIC VARIABLES ON THE NEGATIVE IMPACT OF UNEMPLOYMENT (NIU) AMONG POSTGRADUATE YOUTH - Saraswat, Sunil; G. R. Rathod (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present study aimed to examine the influence of demographic factors on the Negative Impact of Unemployment (NIU) Scale among postgraduate unemployed youth in Madhya Pradesh, India. The NIU Scale, developed by the researcher, is a psychometric tool designed to assess the adverse effects of unemployment across three domains: unrest, mental health issues, and personal life issues. A total of 83 unemployed postgraduates participated in the study. Using One Way Analysis of Variance (ANOVA) and Independent t-test at the 0.05 significance level, the findings indicated significant variations across age, gender, and family income groups. Respondents aged 30–32 years recorded the highest NIU scores, suggesting that prolonged joblessness intensifies its negative impact. Gender differences were highly significant, with males reporting higher NIU scores than females, reflecting the cultural expectation of men as financial providers. Similarly, family income showed a strong effect, with youth from lower-income households (₹5,001–10,000) experiencing greater negative consequences compared to those from higher-income groups. Overall, the study concludes that unemployment is not merely an economic issue but a multidimensional challenge influencing the psychological and social well-being of educated youth.